Local food supply chain resilience to constitutional change: the Brexit effect. Issue 3 (3rd May 2019) - Hendry, Linda Caroline; Stevenson, Mark; MacBryde, Jill; Ball, Peter; Sayed, Maysara; Liu, Lingxuan
Abstract : Purpose: The purpose of this paper is to investigate how local supply chains prepare for and respond to the threats and opportunities presented by constitutional change, thereby building resilience. Design/methodology/approach: Multiple case study analysis of 14 firms in the food sector is presented in the context of the UK's impending exit from the European Union (Brexit). Organisations studied include farmers, processors, retailers and non-government organisations (NGOs). Data from interviews and roundtable discussions has been interpreted using the dynamic capabilities perspective, covering the sensing, seizing, and transforming stages. Findings: The data highlights the importance of both vertical and horizontal collaboration between supply chain actors as they seek to anticipate the impact of the disruption and influence the future shape of the constitution. There is also evidence to suggest firms in possession of dynamic capabilities can innovate to build resilience and enhance their competitive position. Characteristics of the disruption posed by constitutional change are identified and contrast with those of many other threats more typically described in the literature. As a result, the process of building resilience is different. Research limitations/implications: The study could be extended to include post-Brexit interviews to further understand the seizing and transforming stages whilst the impact of Brexit on actors that remain within the EU could also be considered. Practical implications: Practitioners need to work together to influence the future shape of the constitution; and they need to reconfigure their operations and supply chains where necessary to become more resilient to the threat posed by Brexit, such as by reducing their reliance on EU funding streams and trade. The study also has policy implications. Originality/value: The first study of supply chain resilience to constitutional change and a rare empirical study of resilience across multiple supply chain tiers.